Răspuns :
Explicație pas cu pas:
[tex] \bf a= \big(3^{11}+3^{10}+3^9 \big): 39 [/tex]
[tex]\bf a= 3^{9} \cdot \big(3^{11 - 9}+3^{10 - 9}+3^{9 -9 } \big): 39 [/tex]
[tex]\bf a= 3^{9} \cdot \big(3^{2}+3^{1}+3^{0} \big): 39 [/tex]
[tex]\bf a= 3^{9} \cdot \big(9+3+1\big): 39 [/tex]
[tex]\bf a= 3^{9} \cdot 13: 39 [/tex]
[tex]\bf a= 3^{8} \cdot 3 \cdot \: 13: 39 [/tex]
[tex]\bf a= 3^{8} \cdot 39: 39 [/tex]
[tex]\bf a= 3^{8} \cdot 1[/tex]
[tex]\bf a= 3^{8} = \purple{\big( 3^{4} \big)^{2} \implies patrat \: perfect}[/tex]